contribution to the development of a system for automated modular design of numerically controlled flexible manufacturing structures for rotational parts in the form of an expert system - Novaković, Dragoljub; Zeljković, Željko; Gatalo, Ratko (Journal of Production Engineering, 1994)
The paper reviews a segment of research aimed at the development of system for automated modular design of Numerically Controlled Flexible Manufacturing structures (NC FMs) for Rotational Parts (RP). The system is based on the Expert System (ES). It is assumed that NC FMs represent complex forms of various systems with emphasized use of heuristics in the design process. Bearing in mind long-term orien¬tation in this research towards the concept of modular design, an attempt is made to point out the complexity of problem which emerges during the process of selection of a rational FM structure variant among many other possible variants for module composition. The ES concept , based on expert system building is proposed to solve this problem. In connection with that the paper introduces the general ES model for FMs design with the knowledge representation and a global inference engine. It also illustrates the rules and clauses regarding the modules as well as the example of the utilization of ES for FMs design. The final part provides a detail of output results for, the developed concept which represents the basis for FMs design on the CAD workstation with implemen¬tation of available software.